Perancangan Strategi Digital Marketing Untuk Meningkatkan Minat Beli Konsumen Pada Produk Tas Kulit : Studi Kasus : PT. Jayuwan Garut - Saepul Jamil, Alwis; Aulawi, Hilmi; Kurniawati, Rina (Institut Teknologi Garut, 2025)
This study aims to design a digital marketing strategy to increase consumer purchase intention for leather bags produced by PT Jayuwan Garut. The Voice of Customer (VoC) approach was applied to explore consumer needs and preferences, which were then translated into technical attributes using the Quality Function Deployment (QFD) method. Thus, the strategies developed are consumer-driven and more targeted. The analysis revealed three main consumer concerns in digital marketing. First, the quality of promotional content with visually appealing elements, such as professional photos and graphic design, plays a crucial role in creating a strong first impression. Second, the ease of finding products through online search is vital, as easily accessible information significantly increases the likelihood of purchase. Third, responsive interaction on social media—such as answering inquiries quickly and politely—helps foster consumer trust and loyalty. Based on these findings, three key strategies are recommended. First, enhancing the quality of promotional content with high-resolution product photos, creative designs, and engaging videos. Second, conducting regular promotions through digital advertisements across platforms (Google Ads, Meta Ads) to expand market reach. Third, applying persuasive techniques through storytelling and influencer marketing so that promotional messages are not only informative but also emotionally engaging. Overall, this strategy is expected to strengthen brand awareness, increase engagement, and drive sales conversion. The study also provides practical contributions for PT Jayuwan Garut in understanding digital consumer behavior and formulating adaptive marketing policies. Beyond the company, the findings can serve as a reference for other MSMEs seeking to leverage digital marketing to enhance competitiveness in the era of Industry 4.0.